Low-Dose Eptifibatide for Tandem Occlusion in Stroke: Safety and Carotid Artery Patency - Jost, A.; Roels, C.; Brown, M.; Janjua, R.; Heck, D. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Maintaining carotid patency and avoiding symptomatic intracranial hemorrhage are competing concerns in tandem occlusions. This study provides data regarding the safety and efficacy of eptifibatide in stroke from tandem occlusion of the extracranial carotid artery and the intracranial carotid or middle cerebral artery.MATERIALS AND METHODS: This is a retrospective analysis of 58 consecutive patients who received low-dose eptifibatide (135-mcg/kg bolus, 1-mcg/kg/min infusion) during treatment of tandem occlusions. Brain imaging and carotid sonography were performed at 24–36 hours. mRS was documented at 90 days, and carotid sonography, at 30–60 days.RESULTS: The median age and NIHSS score were 64 years and 15, respectively. Twenty-five patients (43%) received tPA. ASPECTSs were 8–10 in 47 (81%) and 5–7 in 11 (19%) patients. Thirty-eight patients had angioplasty/stent placement acutely; 20 had angioplasty alone. Symptomatic intracranial hemorrhage occurred in 1 patient (2%). TICI 2b or higher was achieved in 56 patients (96%). Fifty-seven of 58 patients had clinical follow-up at 90 days (1 lost to follow up). The 90-day mRS was 0–2 in 42 patients (72%). There were 4/58 (7%) re-occlusions within 24–36 hours, all originally treated with stent placement. Forty-nine of 53 surviving patients had carotid sonography at 30–60 days, with 3 delayed re-occlusions, 2 with stents and 1 with angioplasty alone. The overall carotid patency at 30–60 days was 42/49 (86%). Carotid re-occlusion was not associated with clinical decline.CONCLUSIONS: Low-dose eptifibatide seemed to be safe in tandem occlusions (symptomatic intracranial hemorrhage, 2%), although asymptomatic cervical carotid artery re-occlusions still occurred in 14% of patients.mTICImodified TICISICHsymptomatic intracranial hemorrhage